Childhood cancer among twins and higher order multiples - Puumala, Susan E. (2009)
Although several studies have found no change or a decreased risk of childhood cancer in twins, few have controlled for potential confounders such as birth weight. We examined the association of birth plurality and childhood cancer in pooled data from five U.S. states (California, Minnesota, New York, Texas, and Washington) using linked birth-cancer registry data. The data, excluding children with Down syndrome or who died before 28 days of life, included 17,672 cases diagnosed 1980–2004 at ages 28 days-14 years and 57,966 controls with all cases and controls born 1970–2004. Analyses were restricted to children weighing ≤ 4,000g at birth. Odds ratios (OR) and 95% confidence intervals (CI) were estimated using unconditional logistic regression adjusting for sex, gestational age, birth weight, birth order, maternal age, maternal race, state of birth, and birth year. Children who were multiples had no difference in risk of cancer overall (OR= 0.93, 95% CI = 0.82–1.07), but a borderline reduced risk of Wilms tumor (OR= 0.65, 95% CI = 0.39–1.09). For children diagnosed under the age of two there was a reduced risk of Wilms tumor (OR= 0.27, 95% CI = 0.09–0.86) and neuroblastoma (OR= 0.46, 95% CI = 0.25–0.84) and an increased risk of fibrosarcoma (OR= 5.81, 95% CI = 1.53–22.11). Higher order multiple birth (triplets or higher) was not associated with childhood cancer. Our analysis suggests that mechanisms other than birth weight and gestational age may influence the lower risk of Wilms tumor and neuroblastoma in multiple births.